Application of Symbolic Interaction, Social Exchange, and Dramaturgical Theories in Librarians’ Interpersonal Communication to Improve Digital Library Information Services - Henky Ahmad Rihal; Anis Masruri (Jurusan Ilmu Perpustakaan dan Informasi Islam Universitas Islam Negerin Datokarama Palu, 2026)
The development of digital services has transformed the pattern of interaction between librarians and library users, shifting from face-to-face communication to technology-based communication. This transformation creates new challenges in maintaining interpersonal closeness and the quality of information services. This study aims to analyze the application of Symbolic Interaction Theory, Social Exchange Theory, and Dramaturgical Theory in understanding the dynamics of librarians’ interpersonal communication in the digital library environment. This research employs a literature review method with a qualitative analytical approach. Data sources were obtained from research findings, journal articles, and relevant scholarly books published between 2018 and 2025. The analysis was conducted through the stages of identification, classification, and synthesis of literature findings, focusing on the application of the main concepts of the three social theories within the context of digital library services. The results indicate that the three social theories provide complementary conceptual frameworks. Symbolic Interaction Theory explains how the meaning of services is constructed through symbols and digital language; Social Exchange Theory highlights the reciprocal balance between librarians and library users in the process of information sharing; while Dramaturgical Theory describes the role strategies of librarians in presenting a professional image in the digital environment. The integration of these three theories strengthens the understanding of the importance of interpersonal communication based on empathy, trust, and professionalism in building effective and humanistic information services in the digital era. This research contributes to the development of a theoretical framework in the study of library communication and provides a conceptual basis for enhancing the interpersonal competencies of digital librarians in the future. Abstrak Perkembangan layanan digital telah mengubah pola interaksi antara pustakawan dan pemustaka, dari komunikasi tatap muka menjadi komunikasi berbasis teknologi. Perubahan ini menimbulkan tantangan baru dalam menjaga kedekatan interpersonal dan kualitas pelayanan informasi. Penelitian ini bertujuan untuk menganalisis penerapan teori interaksi simbolik, teori pertukaran sosial, dan teori dramaturgi dalam memahami dinamika komunikasi interpersonal pustakawan di lingkungan perpustakaan digital. Penelitian menggunakan metode literature review dengan pendekatan kualitatif analitis. Sumber data diperoleh dari hasil penelitian, artikel jurnal, dan buku ilmiah yang relevan pada periode 2018–2025. Analisis dilakukan melalui tahapan identifikasi, klasifikasi, dan sintesis terhadap temuan literatur dengan fokus pada penerapan konsep-konsep utama dari ketiga teori sosial tersebut dalam konteks layanan digital. Hasil penelitian menunjukkan bahwa ketiga teori sosial memberikan kerangka konseptual yang saling melengkapi. Teori interaksi simbolik menjelaskan bagaimana makna layanan dibangun melalui simbol dan bahasa digital; teori pertukaran sosial menyoroti keseimbangan timbal balik antara pustakawan dan pemustaka dalam proses berbagi informasi; sedangkan teori dramaturgi menggambarkan strategi peran pustakawan dalam menampilkan citra profesional di ruang digital. Integrasi ketiga teori ini memperkuat pemahaman tentang pentingnya komunikasi interpersonal berbasis empati, kepercayaan, dan profesionalitas dalam membangun layanan informasi yang efektif dan humanis di era digital. Penelitian ini berkontribusi pada pengembangan kerangka teoretis dalam kajian komunikasi kepustakawanan, serta memberikan dasar konseptual bagi peningkatan kompetensi interpersonal pustakawan digital di masa depan.